2016
DOI: 10.3171/2015.8.jns151204
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in identification of the frontal language area in patients with dominant frontal gliomas that involve the pars triangularis

Abstract: OBJECTIVE Identification of language areas using functional brain mapping is sometimes impossible using current methods but essential to preserve language function in patients with gliomas located within or near the frontal language area (FLA). However, the factors that influence the failure to detect language areas have not been elucidated. The present study evaluated the difficulty in identifying the FLA in dominant-side frontal gliomas that involve the pars triangularis (PT) to determine the factors that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Surgery was performed according to the previously published concept of information-guided brain tumor removal with the goal of maximal resection of the tumor with minimal risk of permanent postoperative neurological deficits. 12,13,16,17 The following methods have been published previously. 17,18 Intraoperative MRI (AIRIS II; Hitachi Medical Corporation) and updated neuronavigation were used routinely.…”
Section: Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…Surgery was performed according to the previously published concept of information-guided brain tumor removal with the goal of maximal resection of the tumor with minimal risk of permanent postoperative neurological deficits. 12,13,16,17 The following methods have been published previously. 17,18 Intraoperative MRI (AIRIS II; Hitachi Medical Corporation) and updated neuronavigation were used routinely.…”
Section: Surgerymentioning
confidence: 99%
“…12,13,16,17 The following methods have been published previously. 17,18 Intraoperative MRI (AIRIS II; Hitachi Medical Corporation) and updated neuronavigation were used routinely. Surgery was generally performed with maximal possible removal of the area defined by enhancement visualized on contrast-enhanced T1-weighted MRI for tumors showing complete or ringed enhancement and suspected to be grade IV gliomas and removal of the area defined by signal hyperintensity on T2-weighted MRI for non-or partially contrast-enhanced tumors suspected to be grade I, II, or III gliomas.…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18][19]. However, even such methods may fail to identify language areas due to complicated and delicate technical problems, lack of patient cooperation, and interpretation of the results [20,21]. A recent study reported the efficacy of intraoperative language network monitoring by means of cortico-cortical evoked potentials (CCEPs) [22].…”
Section: Introductionmentioning
confidence: 97%